2011
DOI: 10.1093/jxb/err217
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of jasmonates and ethylene in Alternaria alternata f. sp. lycopersici toxin-induced tomato cell death

Abstract: Previous studies have shown that an ethylene (ET)-dependent pathway is involved in the cell death signalling triggered by Alternaria alternata f. sp. lycopersici (AAL) toxin in detached tomato (Solanum lycopersicum) leaves. In this study, the role of jasmonic acid (JA) signalling in programmed cell death (PCD) induced by AAL toxin was analysed using a 35S::prosystemin transgenic line (35S::prosys), a JA-deficient mutant spr2, and a JA-insensitive mutant jai1. The results indicated that JA biosynthesis and sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 59 publications
2
36
0
1
Order By: Relevance
“…Seedlings were grown in a greenhouse, with temperature ranging from 22 to 28 °C (night and day air temperature, respectively) and a 16/6 light/dark cycle. Three weeks after germination, seedlings were transplanted to plastic pots (12cm diameter, 15cm depth) filled with perlite and turfy soil (3:1, v/v), which were watered daily and fertilized weekly with a half-strength Enshi nutrient solution (Zhang et al , 2011). Tomato plants of 7 weeks of age were used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seedlings were grown in a greenhouse, with temperature ranging from 22 to 28 °C (night and day air temperature, respectively) and a 16/6 light/dark cycle. Three weeks after germination, seedlings were transplanted to plastic pots (12cm diameter, 15cm depth) filled with perlite and turfy soil (3:1, v/v), which were watered daily and fertilized weekly with a half-strength Enshi nutrient solution (Zhang et al , 2011). Tomato plants of 7 weeks of age were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…For reverse transcription, oligo(dT)18 primers, 10mM dNTP mix, and water were added to 5 µg RNA, following the manufacturer’s protocol (Fermentas, Canada). Quantitative PCR was performed as described previously (Zhang et al , 2011). All experiments were repeated twice, with similar results.…”
Section: Methodsmentioning
confidence: 99%
“…Coronatine-deficient mutants of Pst DC3000 are reduced in disease-associated necrosis and chlorosis (Brooks et al, 2004(Brooks et al, , 2005. It has been reported that JA is also essential in FB1-and AALinduced cell death (Asai et al, 2000;Zhang et al, 2011). Interestingly, the Atdpl1 mutant is more sensitive to FB1 treatment (Tsegaye et al, 2007).…”
Section: Interconnections Between Sphingolipids and Defense Mechanismsmentioning
confidence: 99%
“…Several studies showed that JA and ET are closely related to AAL toxin induced PCD11. During AAL toxin induced PCD process in Arabidopsis loh2 mutant (a T-DNA knockout mutant of a homologue of the tomato Asc gene), ET-responsive genes were up-regulated within seven hours, but JA pathway related genes were unchanged, and there was no indication of JA accumulation12.…”
mentioning
confidence: 99%